2020
DOI: 10.1080/00016357.2020.1730436
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory outcomes after a 1-year treatment of obstructive sleep apnoea with bibloc versus monobloc oral appliances: a multicentre, randomized equivalence trial

Abstract: Objective: The benefit of bibloc over monobloc appliances in treating obstructive sleep apnoea (OSA) has not been evaluated in randomized trials. We hypothesized that these types of appliances would be equally effective. Material and methods: In this multicentre, randomized equivalence trial, patients with OSA received one type of bibloc or one type of monobloc treatment. At baseline, a 1-night polygraphy study was done, and this was repeated after 1 year. The outcome was any change in the apnoea-hypopnoea ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Table 1 reports the results of the individual studies. Seven studies [29][30][31][32]36,37,54 assessed the adherence only in terms of nights per week: all of them reported a mean nights per week adherence greater than 4. All the studies that assessed the adherence in term of hours per night [33][34][35]42,47,48,53 reported a mean adherence greater than 5.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 reports the results of the individual studies. Seven studies [29][30][31][32]36,37,54 assessed the adherence only in terms of nights per week: all of them reported a mean nights per week adherence greater than 4. All the studies that assessed the adherence in term of hours per night [33][34][35]42,47,48,53 reported a mean adherence greater than 5.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…26,[33][34][35][40][41][42][43][44][45]47,48,50,53,55 Since only one study reported data of MB MAD, 57 it was excluded. Other 16 studies were excluded: 12 because they did not report the data , [27][28][29][30][31][32]36,37,49,51,52,54 three studies reported only a range of values 38,39,46 and one study because it reported only a range of values without the standard deviation or the p-value referred to baseline data. 56 Concerning the nights per week adherence, seven studies were included in the quantitative syntheses.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Después de este periodo de tiempo, fue concluyente que ambos aparatos lograron muy buenos resultados disminuyendo drásticamente las alteraciones respiratorias durante el sueño. Sin embargo, los autores declararon que varios participantes que utilizaron el bibloque abandonaron el ensayo 21 .…”
Section: Discussionunclassified